Compasses, beauty queens and other PCs: Pictorial metaphors in computer advertisements - Forceville, Charles (HERMES - Journal of Language and Communication in Business, 2000)
Computer advertisements make extensive use of pictorial metaphors. The model pro-posed in Forceville (1996) is used as a starting point to analyze 27 advertisements in PC Magazine, July/August 1999 (American edition) that contain a pictorial metaphor. The aim is twofold: (1) to further contribute to the theory of pictorial metaphor by testing the model against a new corpus; (2) to make an inventory of the source domains used in the metaphors,andtherebytomakesome observations about the ways in which represen-tations of computer technology interact with our daily lives.